Learning to read words: the effects of Internet-based software on the improvement of reading performance. - Englert CS; Zhao Y; Collings N; Romig N (Remedial & Special Education)
Two design experiments were conducted to improve the word recognition performance of students at risk of school failure. In Study 1, an Internet-based software from the TELE-Web project was used to remediate the word recognition performance of 4 students at risk of retention and reading disabilities in first grade. In Study 2, the Internet-based software was used with an entire classroom of first-grade students in an effort to prevent reading difficulties and to accelerate reading performance. The results indicated that TELE-Web was effective in improving sight-word recognition and that these improvements transferred to a standardized measure of reading achievement. These findings suggest the promise of Internet-based software in supporting the reading programs of young readers at risk for retention or referral